2007
DOI: 10.1177/1744629507080791
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of positive behavioural support for people with very severe challenging behaviours in community-based settings

Abstract: This study employs a multiple baseline across individual design to describe positive behaviour support for five people in community settings. The individuals represent all people with intellectual disability residing in one county with long-standing challenging behaviour resulting in serious physical injury. Five types of outcome are presented: rates of behaviour, rates of medication, psychiatric symptomatology, quality of life and revenue costs. The systems of support required to maintain outcomes and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 15 publications
2
60
0
Order By: Relevance
“…Two excellent studies were reported by McLean and Grey (2007) and McLean, Grey and McCracken (2012) concerning the use of positive behavioral support with people who have more severe intellectual impairments, some of whom also had autism. What characterizes their work with these nine individuals are very detailed background assessments concerning medical, psychiatric, communicative and cognitive and environmental factors, alongside a functional assessment of the behavior obtained through careful observation.…”
Section: Applied Behavior Analysismentioning
confidence: 99%
“…Two excellent studies were reported by McLean and Grey (2007) and McLean, Grey and McCracken (2012) concerning the use of positive behavioral support with people who have more severe intellectual impairments, some of whom also had autism. What characterizes their work with these nine individuals are very detailed background assessments concerning medical, psychiatric, communicative and cognitive and environmental factors, alongside a functional assessment of the behavior obtained through careful observation.…”
Section: Applied Behavior Analysismentioning
confidence: 99%
“…The effectiveness of a PBS approach has been demonstrated in a variety of home, school, and community settings (Duda, Clarke, Fox, & Dunlap, 2008;R. E. March & Horner, 2002;McClean, Grey, & McCracken, 2007). Research has demonstrated positive outcomes using PBS with typically developing children (Horner et al, 2009), children and youth with behavior disorders (Dunlap, Clarke, & Steiner, 1999), and children with autism and other developmental disabilities (Blair, Fox, & Lentini, 2010).…”
Section: Positive Behavior Supportmentioning
confidence: 99%
“…Furthermore, the view that one can ‘fix’ challenging behaviour by means of short term intervention is clearly not in line with research evidence (cf. Bird & Luiselli 2000; McClean et al . 2007).…”
Section: Introductionmentioning
confidence: 99%